(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Introduction: Majority of childhood fractures occur due to high impact trauma and immediate fracture management is crucial for future healing process. While treating fractures in children it is often a missed opportunity to assess osteopenia risk factors such as poor calcium intake, vitamin D de?ciency, and sedentary life style. However, many fractures are related to bad bone health. This study aims to estimate the burden of vitamin D deficiency (VDD) in pediatric population with fracture, so that timely intervention and strategy to replace vitamin D can be taken. Methods: This study was conducted at Department of Orthopedic and Accident and Emergency Department, Jinnah postgraduate medical center, Karachi, from July 2019 to June 2020. Three hundred and forty five pediatric patients with fracture confirmed by X-ray were included to observe the vitamin D deficiency. Blood sample was taken from the accessible peripheral vein in vacutainer without additives. Serum 25(OH) D was measured and all the information were recorded in predesigned proforma. Results: The average age of the children was 9.10±3.76 years317 (91.88%) were boys and 28 (8.12%) girls. Frequency of vitamin D deficiency in pediatric fractures was observed in 34.20% (118/345). Rate of VDD was significantly high in those children whose BMI was less and equal to 20 kg/m2. Duration of fracture, cause of fracture and traumatic cause were also stratified for VDD but insignificant difference was observed. Conclusion: The results of this study concluded that, vitamin D deficiency in pediatric population presenting with bone fractures is very high. Physicians who treat such children should take proper dietary history and notify the patient and their parents about the high level of prevailing vitamin D deficiency. The clinician should also advice regarding vitamin D supplementation and also notes the presence of potential risk factors. Vitamin D measurement and appropriate replacement can be considered in children who present with a fracture.